Nucleoid-Associated Protein HU: A Lilliputian in Gene Regulation of Bacterial Virulence - Stojkova, Pavla; Spidlova, Petra; Stulik, Jiri (Frontiers in cellular and infection microbiology, 2019)
Nucleoid-associated proteins belong to a group of small but abundant proteins in bacterial cells. These transcription regulators are responsible for many important cellular processes and also are involved in pathogenesis of bacteria. The best-known nucleoid-associated proteins, such as HU, FIS, H-NS, and IHF, are often discussed. The most important findings in research concerning HU protein are described in this mini review. Its roles in DNA compaction, shape modulation, and negative supercoiling induction have been studied intensively. HU protein regulates bacteria survival, growth, SOS response, virulence genes expression, cell division, and many other cell processes. Elucidating the mechanism of HU protein action has been the subject of many research projects. This mini review provides a comprehensive overview of the HU protein.
Keywords: regulace genové exprese u bakterií; bakteriální proteiny; DNA vazebné proteiny; vazba proteinů; Bacterial Proteins; posttranslační úpravy proteinů; virulence; DNA, Bacterial; Gene Expression Regulation, Bacterial; DNA; Virulence; Protein Binding; Protein Processing, Post-Translational; DNA bakterií; DNA-Binding Proteins